Kibersporta žurnālistika: žanriski retoriskais aspekts. - Kisko, Ēriks (Latvijas Universitāte, 2016)
Darbs ir veltīts žanriski retoriskais aspekti izpetījumu. Tā mērķis – definēt žanriski retoriskais aspekti kibersporta publicistikā. Autors veic publiciskas tekstus analitisko analīzi. Īpaša uzmanība darbā tiek veltīta ritoriskajam aspektiem kibersportas interneta vīdē. Darbs sastāv no divām nodaļām. Pirmā nodaļa ir veltīta interneta komunikacija ritoriskam un žanram teoretiskajiem jautājumiem. Otrajā nodaļā tiek analizētas kibersporta interneta tekstus īpatnības. Pētījums var ieinteresēt filologus, kas nodarbojas ar līdzīgiem jautājumiem, kā arī citus interesentus.

The work is dedicated to the research of genre-rhetorical aspect of the cybersport publicity texts. Its aim is to characterise the genre-rhetorical aspects of the cybersport publicity in our days. The author, using the analytical analysis method, is analysing the texts of big internet portal that are dedicated to the cyber sports and specifying the specific genre and rhetorical issues of these texts. In this research, a lot of attention has been brought to the rhetoric of the cyber sports community and its influence on the genre structure of cyber sports publicity texts. The research is divided in two parts. The first part is dedicated to the general theoretical questions that are necessary to execute the research. In the second part, according to and consequently with the tasks set in the first part, the genre-rhetorical aspects of the texts are determined. The research may interest the linguists that are dealing with the similar problems, as well any of the interested readers.
Cybersport Journalism: The Genre and Rhetorical Aspect.
Keywords: Valodniecība; Interneta komunikācija; interneta žanri; interneta kopiena; kibersports; kibersporta publicistika